2014
DOI: 10.1007/s12094-014-1220-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of recurrence and specific survival between luminal A and luminal B breast cancer according to recent changes in the 2013 St Gallen immunohistochemical classification

Abstract: GH3, PR, and Ki67 may all be discriminatory factors for metastasis and specific mortality. Therefore, we suggest including GH3 in the luminal B subtype in the absence of Ki67.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
15
0
2
Order By: Relevance
“…Prat et al. [30] proposed that the IHC‐based definition of luminal A‐like breast cancer is HR positivity, HER2 negativity, Ki‐67 index <14%, and PR expression >20% which led to the modification of the definition of luminal A‐like breast cancer in the 2013 St. Gallen criteria [21]. When the concordance between the 2013 St. Gallen criteria and the Surexam® 21‐gene RS / IHC3 model were calculated in the present study, we observed that almost all patients with luminal A‐like breast cancer were categorized in the RS <26 and pLR groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prat et al. [30] proposed that the IHC‐based definition of luminal A‐like breast cancer is HR positivity, HER2 negativity, Ki‐67 index <14%, and PR expression >20% which led to the modification of the definition of luminal A‐like breast cancer in the 2013 St. Gallen criteria [21]. When the concordance between the 2013 St. Gallen criteria and the Surexam® 21‐gene RS / IHC3 model were calculated in the present study, we observed that almost all patients with luminal A‐like breast cancer were categorized in the RS <26 and pLR groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the patients were stratified into luminal A‐like and luminal B‐like (HER2‐negative) groups based on the 2013 St. Gallen criteria [21]. The luminal A‐like group (deemed to have low‐recurrence risk) included patients with ER‐positive breast cancer, PR expression ≥20%, HER2‐negative breast cancer, and Ki‐67 index <14%.…”
Section: Methodsmentioning
confidence: 99%
“…The analyses were visualized as heat maps. As luminal type breast cancer can be divided into two subgroups, luminal A and luminal B [ 17 ], the differentially expressed genes in luminal breast cancer patients were extracted for cluster analysis to evaluate the efficacy of the proposed method for subdividing this single breast cancer subtype into personalized subgroups. The basal-like type of breast cancer was then analyzed to identify intrinsic subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…Os estudos brasileiros mostram resultados de SLD para câncer de mama, subtipo luminal, de 93,38% 11 . Dentre estudos internacionais, as taxas de sobrevida para o subtipo luminal variam entre 93,3 12 , 96,0 13 e 94,0% 14 , e a heterogeneidade observada nos resultados pode ser resultado de diferenças metodológicas 15 .…”
Section: Resultsunclassified
“…A média de idade de 57,8 anos observada nesta coorte também apresenta similaridade com as análises obtidas em outro estudo 15 , indicando a necessidade de solicitação de mais exames na menopausa, tais como a mamografia. 16 .…”
Section: Resultsunclassified